2011
DOI: 10.1007/s00423-011-0882-8
|View full text |Cite
|
Sign up to set email alerts
|

Green tea protects human osteoblasts from cigarette smoke-induced injury: possible clinical implication

Abstract: Our data suggest possible beneficial effects on bone homeostasis, fracture healing, and bone mineral density following a GTE-rich diet or supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 52 publications
2
34
0
1
Order By: Relevance
“…Green tea contains naturally occurring polyphenols, which are known to have anti-oxidative properties. Although no clinical trials have been published, in vitro studies suggest that green tea might have beneficial effects on osteoblasts [46,47]. In South America, Yerba Mate tea consumption is often preferred to coffee or black tea.…”
Section: Non-alcoholic Beveragesmentioning
confidence: 97%
“…Green tea contains naturally occurring polyphenols, which are known to have anti-oxidative properties. Although no clinical trials have been published, in vitro studies suggest that green tea might have beneficial effects on osteoblasts [46,47]. In South America, Yerba Mate tea consumption is often preferred to coffee or black tea.…”
Section: Non-alcoholic Beveragesmentioning
confidence: 97%
“…We also found that drinking tea could increase the risk of skeletal fluorosis. A previous study (Holzer et al, 2011) showed that regular consumption of tea increases urinary calcium excretion, resulting in bone loss. Furthermore, tea contains fluorine, which is easily released into the water during the tea brewing process (Malde et al, 2003).…”
Section: The Impact Of Water Drinking Habits On Skeletal Fluorosismentioning
confidence: 98%
“…Recently, Holzer et al (2012) [70], showed that green tea extract (GTE) with high levels of polyphenols (mainly catechins) may influence bone mineral density (BMD) in smokers by reducing their oxidative stress levels and enhancing viability of osteoblasts, thus on doing so, supporting bone healing in general. They conclude that dietary supplementation with GTE appears to be an effective and simple way to counter high reactive oxygen species (ROS) level due to cigarette smoke.…”
Section: Effects Of Polyphenols On Bone Metabolismmentioning
confidence: 99%